Cefadroxil-Mupirocin Integrated Electrospun Nanofiber Films for Burn Wound Therapy - Rashid, Saman; Ijaz, Munaza; Rafique, Sana; Yasin, Haya; Mushtaq, Mahnoor; Khan, Abida Kalsoom; Khan, Madiha; Nasir, Bushra; Murtaza, Ghulam (Current Drug Delivery, 2025)
<span class=
Keywords: Polyvinyl alcohol